Post-approval upper airway stimulation predictors of treatment effectiveness in the ADHERE registry. Issue 1 (3rd January 2019) - Heiser, Clemens; Steffen, Armin; Boon, Maurits; Hofauer, Benedikt; Doghramji, Karl; Maurer, Joachim T.; Sommer, J. Ulrich; Soose, Ryan; Strollo, Patrick J.; Schwab, Richard; Thaler, Erica; Withrow, Kirk; et al.
Upper airway stimulation (UAS) has been shown to reduce severity of obstructive sleep apnoea. The aim of this study was to identify predictors of UAS therapy response in an international multicentre registry. Patients who underwent UAS implantation in the United States and Germany were enrolled in an observational registry. Data collected included patient characteristics, apnoea/hypopnoea index (AHI), Epworth sleepiness scale (ESS), objective adherence, adverse events and patient satisfaction measures. Post hoc univariate and multiple logistic regression were performed to evaluate factors associated with treatment success. Between October 2016 and January 2018, 508 participants were enrolled from 14 centres. Median AHI was reduced from 34 to 7 events·h −1, median ESS reduced from 12 to 7 from baseline to final visit at 12-month post-implant. In post hoc analyses, for each 1-year increase in age, there was a 4% increase in odds of treatment success. For each 1-unit increase in body mass index (BMI), there was 9% reduced odds of treatment success. In the multivariable model, age persisted in serving as statistically significant predictor of treatment success. In a large multicentre international registry, UAS is an effective treatment option with high patient satisfaction and low adverse events. Increasing age and reduced BMI are predictors of treatment response. In this largest international report to date, a substantial improvement in OSA severity in response to UAS is identified. Increasing age and reduced BMI are predictors of UAS. http://ow.ly/mtGa30mmTib